THE PEDAGOGICAL FOUNDATIONS OF MORAL EDUCATION IN YUSUF HOS HAJIB'S WORK "KUTADGU BILIG" - Xushnutova Mohigul Ulugbekovna (Web of Journals Publishing, 2025)
This article explores Yusuf Khos Hajib's Kutadgu Bilig, highlighting its insights into educational and moral perspectives. The work examines the role of moral and pedagogical principles in fostering students' moral development.
Keywords: “Kutadgu bilig”, pandnoma, ethics, perfect human education, educational significance, science.